Identical graphs chart a dubious picture. - Hellemans, A. (IEEE spectrum)
For two years now, the nanoelectronics community has wondered at an amazing series of new developments flowing from Lucent Bell Laboratories (Murray Hill, NJ). A flood of papers, 17 of which appeared in the journals Nature and Science alone, reported tantalizing new results in the fast-growing area of nano- and molecular electronics. The lead author of all those papers was Jan Hendrik Schon, suddenly the object of serious suspicions regarding many of the results he published, or at least his manner of publishing them. At 31 years of age, Schon is the author or coauthor of about 200 scientific papers, often the lifetime output of a prolific scientist. Lightning struck when several newspapers, closely followed by Nature and Science, reported that scientists had discovered identical graphs in Schon's papers representing measurements on different devices and published in different journals. The management of Lucent Bell Labs responded quickly to the Schon crisis by setting up an investigative committee. They hope to report by the end of the summer whether scientific fraud has in fact been committed. About a dozen papers are identified that could pose problems, many of them reporting important results